Analysis of Factors Causing Employee Stress in the Work Environment: A Grounded Theory Study - Ricki Threezardi; Retno Dwirahmawati; Yudi Nugraha; Jerry Heikal (Jurnal Sosial Teknologi, 2026)
Background: Stress at work is a common thing for us as humans. Stress is feedback that must be passed by humans in doing a job. Objective: This study aims to deeply understand the experience of work stress in office employees of various ages and positions. Methods: Using a grounded theory approach, this research uncovered the phenomenon of work stress from the subjective perspective of the employees. Seven participants from various backgrounds were involved in in-depth interviews conducted through Google Meet and recorded using Google Docs. Data analysis resulted in the finding that work stress in office employees is influenced by various factors. Through the grounded theory method, we found that there were 25 codes, 9 categories and 4 major themes with a total score of 31. From the data, we found that the major themes that contribute to causing work stress in employees are responsibility, environment, leadership and employee rights. Results: The findings of this study can be used to develop more effective intervention programs in reducing work stress and improving employee well-being. The findings contribute to a more comprehensive understanding of the experience of work stress in the context of office work in Indonesia. The implication of this research is the need for company management to better understand the factors that cause stress for their employees. Conclusion: This research is expected to make a significant contribution to the field of human resource management and occupational health.